2022
DOI: 10.3389/fpls.2022.976684
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated analysis of small RNAs, transcriptome and degradome sequencing reveal the drought stress network in Agropyron mongolicum Keng

Abstract: Agropyron mongolicum (A. mongolicum) is an excellent gramineous forage with extreme drought tolerance, which lives in arid and semiarid desert areas. However, the mechanism that underlies the response of microRNAs (miRNAs) and their targets in A. mongolicum to drought stress is not well understood. In this study, we analyzed the transcriptome, small RNAome (specifically the miRNAome) and degradome to generate a comprehensive resource that focused on identifying key regulatory miRNA-target circuits under drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…In Agropyron mongolicum, five miRNAs including osa-miR444a-3p.2, bdi-miR408-5p_1ss19TA, taemiR9774_L-2R-1_1ss11GT, ata-miR169a-3p, and bdi-miR528-np3_2ss15TG20CA were identified that target drought-associated genes such as MADS47T, CCX1, carC, PAO2, and HOX24 that are involved in the regulation of brassinosteroid (BR) mediated signaling pathway, Na + /K + transport, hydrolase activity, and oxidation-reduction process, respectively (Fan et al, 2022). Similarly in Dendrobium huoshanense and grapevine, a miR156 was identified that targets SQUAMOSA-promoter binding protein-like (SPL) and VvSBP8, VvSBP13, respectively that regulate the development of lateral roots under drought stress conditions.…”
Section: Mirnas-mediated Regulation Of Drought Stress Responsementioning
confidence: 99%
“…In Agropyron mongolicum, five miRNAs including osa-miR444a-3p.2, bdi-miR408-5p_1ss19TA, taemiR9774_L-2R-1_1ss11GT, ata-miR169a-3p, and bdi-miR528-np3_2ss15TG20CA were identified that target drought-associated genes such as MADS47T, CCX1, carC, PAO2, and HOX24 that are involved in the regulation of brassinosteroid (BR) mediated signaling pathway, Na + /K + transport, hydrolase activity, and oxidation-reduction process, respectively (Fan et al, 2022). Similarly in Dendrobium huoshanense and grapevine, a miR156 was identified that targets SQUAMOSA-promoter binding protein-like (SPL) and VvSBP8, VvSBP13, respectively that regulate the development of lateral roots under drought stress conditions.…”
Section: Mirnas-mediated Regulation Of Drought Stress Responsementioning
confidence: 99%
“…The regulatory functions of miRNAs have been identified in different crops. , Degradome sequencing analysis revealed that ppe-MIR169i-p5_2ss17GT19TG is potentially important for drought stress in Medicago ruthenica . Using transcriptome, miRNAome, and degradation genome analyses, Fan et al identified five hub genes and their regulated/targeted miRNAs in the drought stress network of Agropyron mongolicum . The miR5075-mediated gene interaction network regulating seed vigor in rice was identified using degradome sequencing .…”
Section: Introductionmentioning
confidence: 99%
“…51 Using transcriptome, miRNAome, and degradation genome analyses, Fan et al identified five hub genes and their regulated/targeted miRNAs in the drought stress network of Agropyron mongolicum. 49 The miR5075mediated gene interaction network regulating seed vigor in rice was identified using degradome sequencing. 52 It is important to note that degradome sequencing does not rely on bioinformatics predictions for miRNA interactions with target genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, until now, there have been no studies exploring the drought-responsive bHLH family genes in A. mongolicum. In a previous investigation that leveraged transcriptome sequencing data obtained from A. mongolicum during different drought treatment periods (NCBI, PRJNA742257 [50]), 23 bHLH genes were identified through bioinformatics screening. Among them, A. mongolicum's AmbHLH148 exhibited significant upregulation in response to drought stress [51].…”
Section: Introductionmentioning
confidence: 99%